Community-acquired pneumonia in infants: Not simply an acute event with complete recovery. (January 2022) - Lapidot, Rotem; Vietri, Jeffrey; Shaff, Melody; Averin, Ahuva; Lonshteyn, Alex; Weycker, Derek; Wasserman, Matt; Farkouh, Ray; Pelton, Stephen I.
Abstract: Background: Pneumonia in infancy has been linked to long-term consequences for the rapidly developing lung. We examined the impact of hospitalized community-acquired pneumonia (CAP) on subsequent respiratory health. Methods: We conducted a retrospective matched-cohort study using the Optum® de-identified Electronic Health Record Dataset (2009–2018). Study population comprised healthy infants hospitalized for CAP ("CAP patients"), and matched comparators without pneumonia ("comparison patients"), before age 2 years. Study outcomes included any chronic respiratory disorder, reactive airway disease (asthma, hyperactive airway disease, recurrent wheezing), and CAP hospitalization occurring between age 2–5 years, and were evaluated overall as well as by age and etiology at first CAP hospitalization. Results: Study population totaled 1, 343 CAP patients and 6, 715 comparison patients. Rates per 100 patient-years and relative rates (RR) of study outcomes from age 2–5 years for CAP patients versus comparison patients were: any chronic respiratory disorder, 11.6 vs. 4.9 (RR = 2.4 [95% CI: 2.1–2.6]); reactive airway disease, 6.1 vs 1.9 (RR = 3.2 [2.6–3.8]); and CAP hospitalization, 1.0 vs 0.2 (RR = 6.3 [3.6–10.9]). Rates of study outcomes were highest among CAP patients who had their initial hospitalization in the second year of life. Conclusions: Infant CAP foreshadows an increased risk of subsequent chronic respiratory disorders, which may be elevated when CAP occurs closer to pre-school age (i.e., age 2–5 years). These findings are most consistent with the hypothesis that inflammation persists beyond the acute stage of pneumonia and plays a role in the development of chronic respiratory sequelae. Highlights: CAP in infancy increases risk of early childhood chronic respiratory disorders. Risk of chronic respiratory disorders is elevated irrespective of CAP etiology. Risk of chronic respiratory disorders is highest with CAP in second year of life.